Cancer-associated fibroblasts in tumor microenvironment - accomplices in tumor malignancy - Liao, Zehuan (2021)
There is much cellular heterogeneity in the tumor microenvironment. The tumor epithelia and stromal cells co-evolve, and this reciprocal relationship dictates almost every step of cancer development and progression. Despite this, many anticancer therapies are designed around druggable features of tumor epithelia, ignoring the supportive role of stromal cells. Cancer-associated fibroblasts (CAFs) are the dominant cell type within the reactive stroma of many tumor types. Numerous previous studies have highlighted a pro-tumorigenic role for CAFs via secretion of various growth factors, cytokines, chemokines, and the degradation of extracellular matrix. Recent works showed that CAFs secrete H2O2 to effect stromal-mediated field cancerization, transform primary epithelial cells, and aggravate cancer cell aggressiveness, in addition to inflammatory and mitogenic factors. Molecular characterization of CAFs also underscores the importance of Notch and specific nuclear receptor signaling in the activation of CAFs. This review consolidates recent findings of CAFs and highlights areas for future investigations.